Cost Effective Tailings Pond and Heap Leach Pad Liners: A Case History - Mark W. Cadwallader (Society for Mining, Metallurgy & Exploration, 1987)
Heap leach mining requires liners in order to contain leaching solutions for both economic and environmental incentives. The use of HDPE geomembrane liners for heap leaching is discussed in this paper. Comparison is made to clay liners, with inclusion of economic considerations. Several heap leach projects incorporating geomembranes are discussed.